An investigation into employees' perceptions of HIV/AIDS stigma and their attitudes and behaviour towards HIV positive colleagues - Anthony, Liezl Elona (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil)--University of Stellenbosch, 2011.